If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 9x = 0 Combine like terms: 6x + 9x = 15x 15x = 0 Solving 15x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '15'. x = 0 Simplifying x = 0
| -4xwhatnumber+16=-116 | | y^2+3x=(-2) | | x+3(x+1)=2[x-2(x+2)]-3 | | 8-4x=24+2x | | 3b-(6-b)=22 | | 4x^2+2x^2=0 | | x^2-3y-4=0 | | y=2-5x | | 2p+4=6p-3 | | 4(5x-3)=30 | | 4x^2+2y^2=12 | | 2w=4-1/2(x+6) | | 9+x^2=36 | | 5(10-1)= | | 72/9+7= | | (43+62+57+2)/3 | | 3p+2+3p=5+15 | | (43+62+57+1)/3 | | 9-32/4= | | y=x^2-7x | | (43+62+57)/3 | | (5+16)/7-2= | | 6(x)=0 | | 9+9+6-5= | | 0.6g+.50g=14 | | 9+x^2=100 | | X^2-4X+2Y=0 | | 0.3x=.50 | | 25*x^2=100 | | 4.4q-5.3-4.2=-0.8q-4.6 | | 5x-4=10x+8 | | 6m^2+7m-c= |